Stroke-associated pneumonia: A bibliometric analysis of worldwide trends from 2003 to 2020. Issue 38 (24th September 2021) - Chen, Yuanyuan; Yang, Hongyan; Wei, Hui; Chen, Yanqin; Lan, Meijuan
Abstract : Abstract: Stroke-associated pneumonia (SAP) is a spectrum of pulmonary infections in patients within 7 days of stroke. Which is one of the most common complications after stroke and is significantly associated with a poor prognosis of stroke. To the best of our knowledge, a bibliometric method was not previously used to analyze the topic of SAP; we aim to describe the situation and evolution of SAP from 2003 to 2020, and to discuss the research hotspots and frontiers. A total of 151 articles were retrieved from the Scopus database. Bibliometric analysis was used to explore the dynamic trends of articles and the top subject areas, journals, institutes, citations, and co-keywords. VOS viewer software (version 1.6.15) was used to graphically map the hot topics of SAP based on the co-keywords. A total of 151 articles were identified. Articles have increased over the recent years and faster in the last 2 years (55 articles, 36.4%), the majority of subject areas are medicine (124 articles, 82.1%) and neuroscience (38 articles, 25.2%). The "Journal Of Stroke And Cerebrovascular Diseases" with 15 articles has been scored as the first rank followed by "Plos One." Regarding the geographical distribution of articles, China is the most productive country with 50 articles (33.1%), others are more prominent in Europe, and most institutes are universities. Citations have increased over time, the main country of the top five highly cited published articles are Germany and before 2008. The co-keywords are mainly divided into four aspects: risk factors, predictive scores, preventions, and outcomes. This study could provide practical sources for researchers to find the top subject areas, journals, institutes, citations, and co-keywords. Moreover, the study could pave the way for researchers to be engaged in studies potentially lead to more articles in this field.